Mitigating land fragmentation: the role of organizational integration in promoting green technology adoption among farmers - Tunio, Raza Ali; Lufeng, Li; Das, Ghansham; Khan, Nawab; Gopang, Aamir Ali (Frontiers in Sustainable Food Systems, 2025)
IntroductionLand fragmentation remains a critical barrier to sustainable agriculture, as it reduces efficiency and hinders the adoption of modern green technologies, particularly in smallholder farming systems.PurposeThis study explores the impact of land fragmentation on farmers' adoption of green technologies and examines how organizational integration can moderate these adverse effects.MethodsPrimary data were collected from 420 crop farmers across four districts of Balochistan, Pakistan. A binary probit model was employed to analyze the effects of land fragmentation and organizational integration on adoption behavior, with controls for education, training participation, land characteristics, and household factors.ResultsThe findings reveal that land fragmentation significantly decreases the likelihood of adopting green technologies, while organizational integration strongly promotes adoption and offsets the negative effects of fragmentation. Moreover, education, participation in training, and machinery acquisition positively influence adoption, whereas high dependence on agricultural income, land transfer, and risk perception serve as barriers.ConclusionPolicies that encourage land consolidation and strengthen cooperative networks are essential. Promoting organizational integration through farmer cooperatives can alleviate the constraints of fragmented farmland, enhance sustainable agricultural practices, and improve rural livelihoods.